The Changing Face of Leadership and School Improvement in English Primary Schools - Jerman, Bill; Jerman, Sarah (Medi@ções, 2018)
The English education system has faced many changes over the last 30 years. This article looks at the impact of these changes on school system leadership and school improvement and the challenges facing education in the future.